(untitled) (Web of Teachers: Inderscience Research, 2024)
Diachronic corpora are essential tools in linguistic research, enabling scholars to analyze how language changes over time. These corpora, consisting of texts from different historical periods, allow researchers to examine shifts in syntax, morphology, semantics, and phonology. This article explores the development and use of diachronic corpora, discusses key challenges such as data sparsity and representativeness, and highlights influential works and researchers in the field, such as Sten Rissanen’s Helsinki Corpus and Douglas Biber’s multi-dimensional analysis of historical texts. Through these corpora, linguists gain valuable insights into the patterns and processes that shape language evolution.